Splenic Development and Injury in Premature Lambs Supported by the Artificial Placenta - McLeod, Jennifer S. (J Pediatr Surg, 2019)
INTRODUCTION: The purpose of this study is to evaluate splenic effects during artificial placenta (AP) support. METHODS: AP lambs (118-121d, n=14) were delivered and placed on the AP support for a goal of 10-14 days. Cannulation used right jugular drainage and umbilical vein reinfusion. Early (ETC;115-120d; n=7) and late (LTC; 125-131d; n=7) tissue controls were delivered and immediately sacrificed. Spleens were formalin fixed, H&E stained, and graded for injury, response to inflammation, and extramedullary hematopoiesis (EMH). CD68 and CD163 stains were used to assess for macrophage activation and density. Clinical variables were correlated with splenic scores. Groups were compared using Fisher’s Exact Test and descriptive statistics. P<0.05 indicated significance. RESULTS: Mean survival for AP lambs was 12±5d. There was no necrosis found in any of the groups. Vascular congestion and sinusoidal histiocytosis did not significantly differ between AP and control groups (p=0.72; p=0.311). There were significantly more pigmented macrophages (p=0.008), CD163 (p=<0.001), and CD68 (p=<0.001) stained cells in the AP group. ETC and LTC demonstrated more EMH than AP spleens (p=<0.001). CONCLUSIONS: During AP support, spleens appear to develop normally and exhibit an appropriate inflammatory response. After initiation of AP support, EMH transitions away from the spleen.